1995
DOI: 10.1677/joe.0.1460449
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid glands: novel sites of growth hormone action

Abstract: Thyroid hormones inhibit the synthesis and release of GH in avian species. This may represent a feedback mechanism, since GH enhances the peripheral production of tri-iodothyronine (T3). The possibility that GH may also have direct effects on thyroidal function was therefore investigated. The basal and thyrotrophin-induced release of thyroxine (T4) from incubated chicken thyroid glands was not enhanced, however, in the presence of chicken GH. Contrarily, GH impaired T4 release in a dose-related way. These acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…GH receptor immunoreactivity has also been reported in other tumor types, such as hepatocellular carcinoma (22) and occasionally in tumors appearing after GH therapy in immunocompromised patients (23). In our cases we found intense diffuse immunoreactivity in papillary carcinoma cells, though note that GH receptors have also been detected in normal thyroid cells of chickens (24), humans and rats (25). Other studies have also demonstrated the presence of the IGF-1 receptor in thyroid papillary carcinomas (26).…”
Section: Discussionsupporting
confidence: 73%
“…GH receptor immunoreactivity has also been reported in other tumor types, such as hepatocellular carcinoma (22) and occasionally in tumors appearing after GH therapy in immunocompromised patients (23). In our cases we found intense diffuse immunoreactivity in papillary carcinoma cells, though note that GH receptors have also been detected in normal thyroid cells of chickens (24), humans and rats (25). Other studies have also demonstrated the presence of the IGF-1 receptor in thyroid papillary carcinomas (26).…”
Section: Discussionsupporting
confidence: 73%
“…[29], and large species-related differences have also been reported (see electronic supplementary material). On the other hand, the lack of significant differences in circulating hormone levels among our specific T3 dosages could be interpreted as a result of a negative feedback regulation to avoid excessive hormone circulation at the end of the experiment [41,56,57]. The dosage-related effects detected on bill redness could, however, be a consequence of differences in plasma levels days before blood sampling.…”
Section: Discussionmentioning
confidence: 87%
“…Historically, many studies have shown that both mammalian TSHs and avian pituitary homogenates stimulate thyroid gland activities (radioiodine uptake, thyroid hormone release, and gland growth; see, e.g., work by MacKenzie, 1981), and these activities are mediated via TSH receptors (Hull et al, 1995).…”
Section: Pituitary Control Of Thyroid Gland Functionmentioning
confidence: 99%
“…The effects of GH on deiodinases vary with deiodinase type and tissue; GH decreases hepatic 5D III (effect at the level of transcription) but does not alter 5 D II in the brain ( Van der Geyten et al, 2001). GH receptors are present in the thyroid and in vitro studies indicate that GH decreases T 4 release from the thyroid and may directly stimulate thyroid gland growth (Hull et al, 1995).…”
Section: Effects On Growth Interactions Between the Thyroid And Growtmentioning
confidence: 99%